GAYA KEPEMIMPINAN DEMOKRATIS DAN VISIONER - Kurniati; Siti Chumaidah; Sudarti; Ahmad Hariyadi; Slamet Utomo (Equity In Education Journal, 2023)
The principal has distinctive characteristics in leading or often referred to as a leadership style in carrying out the wheels of the school organization that he leads. Leadership style is a way for leaders to influence their subordinates to want to work together productively to achieve organizational goals. This conceptual article aims to examine the phenomenon of democratic and visionary leadership in improving the performance of teachers in Elementary School (SD) 1 Colo Kudus. Based on the results of the study, it can be concluded that the combination of democratic and visionary leadership styles is very suitable to be applied at SD 1 Colo Kudus to improve teacher performance. Various innovative ideas from school principals for the improvement and progress of schools, including those for improving teacher performance, are always brought together and discussed in advance with teachers to obtain various responses and input; henceforth the final decision remains in the hands of the principal. Based on the results of this study, a combination of democratic and visionary leadership styles can be an alternative that can be applied to improve teacher performance in other basic education units.